2022
DOI: 10.1002/smsc.202200076
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose: Recent Advances Toward Biomedical Applications

Abstract: Sustainable materials are key to the continual improvement of living standards on this planet with minimal environmental impacts. Nanocellulose combines the fascinating features of nanomaterials with favorable properties of the abundantly available cellulose biopolymer, which in recent years has gained much attention toward biomedical applications by virtue of its unique surface chemistry, remarkable physical features, and inherent biological attributes. Herein, the recent advances in nanocellulose‐based biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 293 publications
0
15
0
Order By: Relevance
“…Auxetic tubular structures have shown promise in biomedical applications [137]. They can be utilized in implantable devices [111,[138][139][140][141], tissue engineering scaffolds [142,143], drug delivery systems [26,142,144], biosensors, and diagnostics [145]. Their unique properties, such as improved flexibility, enhanced surface area, and compatibility with biological tissues, make them attractive for various biomedical applications.…”
Section: Biomedical Devicesmentioning
confidence: 99%
“…Auxetic tubular structures have shown promise in biomedical applications [137]. They can be utilized in implantable devices [111,[138][139][140][141], tissue engineering scaffolds [142,143], drug delivery systems [26,142,144], biosensors, and diagnostics [145]. Their unique properties, such as improved flexibility, enhanced surface area, and compatibility with biological tissues, make them attractive for various biomedical applications.…”
Section: Biomedical Devicesmentioning
confidence: 99%
“…Wood-derived cellulose nanofibrils (CNFs) are a promising material for the development of wound dressings. , This nanomaterial consists of individual fibrils with a diameter of 2–10 nm and a length of several micrometers that arrange into 20–50 nm thick aggregates. CNFs form colloidal suspensions in water with a three-dimensional (3D) network maintained by the entanglement of the fibers, hydrogen bonds, and van der Waals and electrostatic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…CNFs are renewable materials derived from nonanimal origins with tunable aspect ratio, surface charge, and physical forms (CNFs can be prepared as gel suspensions, self-standing hydrogels, foams, or films). These properties have led to CNFs being a topic of intense interest in wound care. ,, The in vitro and in vivo wound-healing properties of CNF-based materials have been demonstrated in acute wound models and burns treatment. In these works, CNF-based wound dressings have improved the time of reepithelialization, were ease to apply, and provided a desirable moist healing environment. However, at the time of writing, the potential of CNFs to accelerate the healing of chronic wounds is not proven.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of its strong biocidal activity, low toxicity, and high abundance, copper has garnered immense interest as an antimicrobial coating agent for decades. Between 2008 and 2011, the US Environmental Protection Agency (EPA) registered over 300 copper alloys as antimicrobials, and their effectiveness against the coronavirus was also recommended in 2021, emphasizing the great potential of copper-containing materials in the manufacturing of self-disinfecting surfaces. Copper nanoparticle (Cu NP)-coated or -impregnated fabrics and textiles have also been explored for potential applications to prevent infection transmission. Nonetheless, the colored metallic copper and Cu­(II)-containing compounds usually require a long contact time of up to hours to eliminate the target, rendering them of limited value in mitigating the lateral transmission of highly infectious pathogens. , In contrast, many earlier studies have shown that the colorless copper­(I) iodide (CuI) exhibits prominent antimicrobial activity and low toxicity that may serve as a more suitable coating precursor. , Most existing methods for CuI coating fabrication, unfortunately, require toxic acetonitrile as the processing solvent due to its poor solubility in other solvent systems . Extensive use of acetonitrile may cause health problems to the workers and a severe impact on the environment.…”
Section: Introductionmentioning
confidence: 99%